The Effect of Blended Learning on Metacognitive Awareness, Self-Efficacy, Learning Independence, and Learning Achievement of Senior High School/MA Students - Akhmad Tajudin Alhaq; Hartono Hartono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of this study is to find out whether there is an influence of blended learning on metacognitive awareness, self-efficacy, student learning independence, and student learning achievement and to find out whether blended learning is superior to scientific learning in mathematics learning in the aspects of metacognitive awareness, self efficacy, student learning independence, and student learning achievement. This research is a pseudo-experimental research with the population of all students in grade XI MAN 2 Wonosobo for the 2023/2024 school year. Of the ten existing classes, two classes were selected by purposive sampling, namely classes XI - 3 and XI - 4. From the two selected classes, then randomly selected so that class XI - 4 was obtained as an experimental class, namely the class that received blended learning and class XI - 3 as a control class that received mathematics learning with scientific learning and vector subjects. The instruments used to collect data are in the form of student learning achievement test questions and questionnaires on metacognitive awareness, self-efficacy, and student learning independence. Validity is determined by the consideration of the validator who concludes that the instrument used in this study is valid. Meanwhile, Cronbach's alpha of all variables in this study showed reliable values. To see if there is an effect of blended learning on metacognitive awareness, self-efficacy, learning independence and student learning achievement after research treatment is carried out in both the experimental and control classes, the T2 hotteling statistical test is used. Meanwhile, to see the advantages of scientific learning with blended learning methods compared to scientific from the perspective of metacognitive awareness, self-efficacy, learning independence and student learning achievement from both classes, univariate t test statistics were used. The results of the study showed that :(1) there was an effect of blended learning on metacognitive awareness, self-efficacy, learning independence, and student achievement simultaneously; (2) scientific blended learning is not superior to scientific in terms of metacognitive awareness, self-efficacy, and learning independence of high school/MA students; (3) scientific blended learning is superior to scientific in terms of learning achievement of high school/MA students.